BUILDING ECOTOURISM ENGLISH VILLAGE WITH VILLAGE REGULATIONS ABOUT TOURISM VILLAGE IN SUMBAWA REGENCY - Yamin, Ahmad; Suparman, Suparman (Jurnal Manajemen Pelayanan Hotel, 2022)
This research is about the innovation of interdisciplinary studies in the fields of law, English, and tourism in building an ecotourism English village with village regulations regarding tourist villages in the Sumbawa district. This study uses a normative legal approach, using a statutory approach, which is carried out by reviewing the laws and regulations related to the legal issues being handled, in this case building an ecotourism English village with Village Regulations. The findings of this study are the village authority to form village regulations regulated in Law Number 6 of 2014 concerning Villages. Furthermore, with the basis of village regulations, it becomes the basis for building an English ecotourism village in Sumbawa Regency. The English ecotourism village concept provides opportunities for the younger generation to explore and build tourism potential that is independent, sustainable, and environmentally friendly. The potentials assembled based on ecotourism English villages include fishing or marine tourism villages, production centers for producing agricultural equipment, making machetes, knives, Sumbawa swords, and coastal tourism supported by mangrove trees and several other types of plants. Furthermore, it was also found that the obstacles to the development of tourist villages, namely the lack of village governments in allocating adequate budgets for the development of tourism village potential so that the presence of tourist villages in several villages in Sumbawa Regency accomplishes not have adequate facilities and infrastructure, and the average tourist village in Sumbawa Regency, there is no village regulation regarding tourist villages. Keywords: Building, English, Ecotourism Village, Village Regulations.